Adverse childhood experiences and multisite pain among adolescents in the United States - Tristin Smith; Dorna Kheirabadi; Yijun Guo; Junzhi Sun; Jennifer Pierce; Rachel S. Bergmans; Kevin F. Boehnke; Andrew Schrepf; Daniel Clauw; Chelsea M. Kaplan; Anne Arewasikporn (PAIN Reports)
Abstract. Introduction:. Childhood adversity can have a lasting negative impact throughout one's life. Youth with pain conditions consistently report a higher rate of adverse childhood experiences (ACEs) when compared with their healthy peers. Adolescents experiencing pain in more than 1 region tend to have greater symptom burden and reduced quality of life. Research on the association between ACEs and multisite pain in adolescents is sparse. Objectives:. The objective of our study was to investigate the association between cumulative ACEs and self-report of multisite pain in early adolescence using data from the Adolescent Brain Cognitive Development study. Methods:. We used a 19-region body map to evaluate the presence of regional pain (1-2 regions) and multisite pain (≥3 regions). We analyzed data using multinominal logistic regression, adjusting for sociodemographic factors including pubertal status, sex, race/ethnicity, and income-to-needs ratio. Results:. We included a total of 7582 children aged 12 to 13 years, with 33.4%, 24.0%, 13.2%, and 8.6% reporting 1, 2, 3, and 4+ ACEs, respectively. Moreover, 30.7%, 24.2%, 15.2%, and 10.1% of children with multisite pain reported 1, 2, 3, and 4+ ACEs, respectively. Those with 4+ ACEs (adjusted odds ratio 1.62, 95% confidence interval 1.24-2.12) and 3 ACEs (adjusted odds ratio 1.44, 95% confidence interval 1.14-1.82) were more likely to report multisite pain compared with the children with no ACEs. Conclusion:. We showed a potential dose–response relationship between cumulative ACEs and multisite pain, suggesting that the impact of ACEs on pain, particularly multisite pain, may emerge earlier than previously documented. Keywords: Adverse childhood experiences, Multisite pain, Adolescent pain